Emergence of Multidrug Resistant Enterococcus Species Isolated from Clinical Samples in North India (Global Journal of Medical Research, 2023)
Background Enterococci species have become increasingly recognized as Multidrug resistant pathogens This study aimed to determine the antimicrobial resistance profile of Enterococcus spp Enterococcus faecalis and Enterococcus faecium from various clinical specimens in Delhi India Methods The study was co nducted at Dr Lal path Labs Delhi from January 2020 to April 2022 Various clinical samples were collected and processed for bacterial isolation and susceptibility testing to antimicrobial agents Samples were inoculated onto blood agar and CHROMagar media only for urine isolates The isolates were identified to genus and species level by cultural characteristics and MALDITOF-MS Sensitivity testing to 11 antimicrobials was done using the VITEKXL broth microdilution method
Keywords: high-level gentamicin resistance (HLGR); vancomycin resistant enterococci (VRE)